EVALUASI IMPLEMENTASI PROGRAM EKSTRAKURIKULER MEWARNAI GAMBAR KELAS 1-3 SDS PAH TSUNG - Faizin Nawarda; Kardiman Kardiman; Isnawati Isnawati; Lolla Amelia Ainun (Institut Pendidikan Tapanuli Selatan, 2022)
Extracurricular activities provide opportunities for students to develop and express their abilities according to their interests when school time is over. Mahogany et. Al. (2005) argue that extracurricular activities are defined as organized activities, adult supervision, emphasizing skill development, and promoting positive student development. Meanwhile, Nelson et. Al. (2002) assumed in their study that extracurricular activities are experiences outside the classroom. Extracurricular activities include non-formal curriculum, volunteer work, and student groups, as well as student clubs and initiatives outside of school. This can occur inside and outside school buildings, as well as after and during school hours (Bîrzéa et al., 2004). In the end, extracurricular activities are non-formal curriculum activities held outside school hours which aim to support and develop students' abilities in certain fields and to build their self-confidence.